A formação em Sanfona na educação superior : reflexões, análises e proposições a partir dos cursos de graduação em música do Brasil - Silva, Hélio Giovanni Medeiros da (2023)
This thesis focuses on (de)coloniality in higher education in music and its implications for teaching popular music, emphasizing the education of the accordion player. It aims to understand and systematize strategies and pedagogical proposals that support the teaching and learning of the accordion in higher education in Brazil's Bachelor of Music degree. The perspectives presented here are based on dimensions of contemporary musical education, singularities of the accordion player's education, and aspects of the instrument's training trajectory in Brazil. The objectives of the research were to raise and understand aspects related to the trajectory and praxis of teaching popular music and the Brazilian accordion in the light of literature; highlight particularities about accordion training recorded in the pedagogical projects of higher education courses in the country; and verify perceptions, perspectives, and problematizations about music training, with an emphasis on accordion teaching in Brazil. Qualitative research provides the methodological approach by including bibliographical research and documentary research. The corpus of documentary research was composed of pedagogical projects of the universities that offer accordion teaching, namely the State University of Rio Grande do Sul, the Federal University of Paraíba, the Federal University of Goiás, and the Faculty of Music Souza Lima. The results showed that, although in the literature there is a significant advance in research that problematizes and reflects on the relevance of teaching music from a decolonial perspective, considering popular knowledge from the geographic context and the student's belonging, these aspects are still considered discreetly on the curricula. Based on these data and the different analyses consolidated throughout the work, this thesis presents propositions and perspectives to contribute.